Source base of researches of mass-circulation newspapers of Ukraine of 1917-1941 - Vakulchuk Olha (Bìblìotečnij vìsnik, 2021)

(untitled)
Mass-circulation press is a group of Soviet publications issued by industrial enterprises, collective farms, state farms, educational institutions, establishments, military units, political departments of MTS, public associations, trade unions, etc. The origin, development, distribution, and functioning of mass-circulation newspapers are closely connected with the Soviet period of history, characterize the entire existence of Soviet power and correspond to the concept of Soviet party ideology that existed for seventy years. The purpose of the paper is to illustrate the necessity fora comprehensive study of mass-circulation newspapers published on the territory of modern Ukraine during 1917-1941 and to determine the source base of such studies. The methodological basis of the work is the principle of historicism. The methods of analysis of historical sources and synthesis of information are used and form the basis for the research of the mass-circulation press. Scientific novelty. Mass-circulation newspapers are presented as an independent object of source studies and historical and bibliographic research; several groups of sources are analyzed, some of them are introduced into scientific circulation for the first time; it is emphasized that the array of mass-circulation newspapers requires the elaboration and systematization from the modern point of view, which involves the creation of a system of traditional and digital library and information resources. Conclusions. Mass-circulation newspapers are a separate type of newspaper periodicals, a unique phenomenon of the Soviet era, a historical source that reflects the methods of influencing the mass consciousness, the formation of labor relations in teams. A comprehensive study of the "small" press would help to fill the gaps in the history of institutions, enterprises, public associations, historical research of the press, as well as become a source for creating a repertoire of national bibliography.